2020
DOI: 10.3389/fphys.2019.01601
|View full text |Cite
|
Sign up to set email alerts
|

Xylooligosaccharide Modulates Gut Microbiota and Alleviates Colonic Inflammation Caused by High Fat Diet Induced Obesity

Abstract: Obesity leads to colonic inflammation and may increase the risk of colorectal cancer. Xylooligosaccharide (XOS) exhibits strong antioxidant and excellent antibacterial properties, and can be utilized by gut microbes to maintain the ecological balance of the intestinal tract. In this study, we explored how XOS modulates the microbiota and regulates high fat diet (HFD) induced inflammation. We measured the changes in body weight and visceral coefficients in rats fed a high-fat diet. We also measured the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…SCFA in the colon content were determined following a previously described method with some modification (40). After dissection, the segmented colon sections were squeezed with sterile forceps, and the contents were removed and stored in cryopreservation tubes at −80 • C. The colon contents were diluted five-fold with ultrapure water and vortexed for 3 min.…”
Section: Determination Of Scfamentioning
confidence: 99%
“…SCFA in the colon content were determined following a previously described method with some modification (40). After dissection, the segmented colon sections were squeezed with sterile forceps, and the contents were removed and stored in cryopreservation tubes at −80 • C. The colon contents were diluted five-fold with ultrapure water and vortexed for 3 min.…”
Section: Determination Of Scfamentioning
confidence: 99%
“…Frontiers in Gastrointestinal Sciences has played a significant role in publishing important papers in the emerging field. These include papers on the role of the gut microbiome in both alcoholic (Su et al, 2016;Yue et al, 2020;Zheng et al, 2020) and non-alcoholic (Bian et al, 2017;Porras et al, 2018;Zheng et al, 2018) liver disease; the role of sulfur metabolism by the microbiome on gut sensory signaling, colonic inflammation and cancer; (Carbonero et al, 2012;Bala et al, 2014;Guo et al, 2016;Burgueño et al, 2019;Fei et al, 2019;Song et al, 2019;Ren et al, 2020) glucose homeostasis and type 2 diabetes; (Lê et al, 2012;Su et al, 2016) tuberculosis (Luo et al, 2017) mood and behavior and Gulf war illness; (Grenham et al, 2011;Kimono et al, 2019) pulmonary tuberculosis; (Luo et al, 2017) and autoimmune pancreatitis (Haruta et al, 2012). Other papers provided information on the effects of xenobiotics, probiotics, vitamins, and medication affect the gut microbiome and physiology (Yang et al, 2015;Su et al, 2016;Atashgahi et al, 2018;Li et al, 2018;Zheng et al, 2018;Chang et al, 2019;Fei et al, 2019;Guan et al, 2019;Song et al, 2019;Xu et al, 2019;Zhu et al, 2020) while some addressed the interplay between endogenous processes and the gut microbiome including bile acids and cholesterol metabolism, adrenergic input and gut epithelial responses (Yang et al, 2017;Burgueño et al, 2019;Molinero et al, 2019).…”
Section: Gastrointestinal Sciencesmentioning
confidence: 99%
“…Consistently, our results showed that abundance of Akkermansia was positively associated with ileal VH and the expression of ZO2 and CLDN1 . Paraprevotella and Prevotella enriched by XOS treatment were also described by a recent research ( Fei et al, 2020 ), in which they were associated with butyrate generation in the gut because of their capability to degrade cellulose and polysaccharides, which was favorable to FCR of animals fed plant-based diets ( Gorvitovskaia et al, 2016 ; Shah et al, 2018 ). Besides, Prevotella abundance was also associated with a higher production of luminal sIgA, implying its role in intestinal immune regulation ( Mach et al, 2015 ).…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, dietary supplementation of prebiotics and synbiotics (both contained 150 mg/kg XOS) improved small intestinal morphology and sIgA content in broilers ( Min et al, 2016 ). Besides, XOS was also demonstrated to mitigate high-fat diet-induced intestinal inflammation and barrier dysfunction by modulating gut microbial composition ( Fei et al, 2020 ). Accordingly, addition of XOS may exert active roles in protecting intestinal function in chickens.…”
Section: Introductionmentioning
confidence: 99%